Mechanisms of Supralinear Calcium Integration in Dendrites of Hippocampal CA1 Fast-Spiking Cells - Camiré, Olivier; Lazarevich, Ivan; Gilbert, Tommy; Topolnik, Lisa (Frontiers in Synaptic Neuroscience, 2018)
In fast-spiking (FS), parvalbumin-expressing interneurons of the CA1 hippocampus, activation of the GluA2-lacking Ca2+-permeable AMPA receptors (CP-AMPARs) in basal dendrites is coupled to the Ca2+-induced Ca2+-release (CICR), and can result in a supralinear summation of postsynaptic Ca2+-transients (post-CaTs). While this mechanism is important in controlling the direction of long-term plasticity, it is still unknown whether it can operate at all excitatory synapses converging onto FS cells or at a set of synapses receiving particular input. Using a combination of patch-clamp recordings and two-photon Ca2+ imaging in acute mouse hippocampal slices with computational simulations, here we compared the generation of supralinear post-CaTs between apical and basal dendrites of FS cells. We found that, similar to basal dendrites, apical post-CaTs summated supralinearly and relied mainly on the activation of the CP-AMPARs, with a variable contribution of other Ca2+ sources, such as NMDA receptors, L-type voltage-gated Ca2+-channels and Ca2+ release. In addition, supralinear post-CaTs generated in apical dendrites had a slower decay time and a larger cumulative charge than those in basal, and were associated with a stronger level of somatic depolarization. The model predicted that modulation of ryanodine receptors and of the Ca2+ extrusion mechanisms, such as the Na+/Ca2+-exchanger and SERCA pump, had a major impact on the magnitude of supralinear post-CaTs. These data reveal that the supralinear Ca2+ summation is a common mechanism of Ca2+ signalling at CP-AMPAR-containing synapses. Shaped in a location-specific manner through modulation of ryanodine receptors and Ca2+ extrusion mechanisms, CP-AMPAR/CICR signalling is suitable for synapse-specific bidirectional modification of incoming inputs in the absence of active dendritic conductances.